Comparative ivermectin plasma concentration profiles after subcutaneous administration of different long-acting formulations to cattle - Leite, Paula (2019)
The current study evaluated the ivermectin comparative pharmacokinetic behaviour and systemic availability following administration of six different available long-acting formulations to cattle. Forty-two healthy calves were randomly allocated into six experimental groups (n=7). Animals in each group were subcutaneously treated at label recommended doses with a different ivermectin formulation (Formulation A= 700 µg/kg; B= 700 µg/kg; C= 630 µg/kg, D= 800 µg/kg; E= 700 µg/kg; F= 630 µg/kg). Blood samples were collected over 120 days post-treatment (14 sampling times). Ivermectin concentrations in plasma were measured by HPLC. A complete pharmacokinetic analysis was performed for all the ivermectin preparations. The mean peak plasma concentration (Cmax) and area under the concentration vs time curves (AUC, drug exposure) obtained for each formulation were compared following dose rate normalization. The statistically significant differences observed among the kinetic parameters reflecting the rate and extent of IVM absorption from the different formulations assayed here, indicate the existence of some differences among preparations in terms of pharmaceutical behaviour. The relationship between the plasma kinetic profiles for the different formulations and the ?theoretical threshold? to obtain an optimal efficacy against ticks was calculated using the period of time in which ivermectin concentrations were above 10 ng/mL. Formulations A, B and D remained above 10 ng/mL for a longer period of time compared to Formulations C, E and F (a highest dose rate of 800 µg/kg was used for formulation D). The available long-acting ivermectin formulations under evaluation showed slight differences in their absorption patterns, which was reflected in the observed plasma pharmacokinetic behavior. Formulations A and B showed the best performance from the pharmacokinetic point of view, showing initial higher ivermectin concentrations followed by a sustained plasma concentration above 10 ng/mL for more than 40 days that may be relevant to obtain an optimal efficacy against ticks.